Community guidelines for GPCR ligand bias: IUPHAR review 32. (27th March 2022) - Kolb, Peter; Kenakin, Terry; Alexander, Stephen P. H.; Bermudez, Marcel; Bohn, Laura M.; Breinholt, Christian S.; Bouvier, Michel; Hill, Stephen J.; Kostenis, Evi; Martemyanov, Kirill A.; Neubig, Rick R.; Onaran, H. Ongun; et al.
Abstract : GPCRs modulate a plethora of physiological processes and mediate the effects of one‐third of FDA‐approved drugs. Depending on which ligand activates a receptor, it can engage different intracellular transducers. This 'biased signalling' paradigm requires that we now characterize physiological signalling not just by receptors but by ligand–receptor pairs. Ligands eliciting biased signalling may constitute better drugs with higher efficacy and fewer adverse effects. However, ligand bias is very complex, making reproducibility and description challenging. Here, we provide guidelines and terminology for any scientists to design and report ligand bias experiments. The guidelines will aid consistency and clarity, as the basic receptor research and drug discovery communities continue to advance our understanding and exploitation of ligand bias. Scientific insight, biosensors, and analytical methods are still evolving and should benefit from and contribute to the implementation of the guidelines, together improving translation from in vitro to disease‐relevant in vivo models.